(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to improve electronic records management in polytechnics necessitated this study. Thestudy ascertained cloud computing competencies required of polytechnic OTMgraduates in NorthEast Nigeria for electronic records management. One research question and two null hypotheses guided the study. The study adopted descriptive survey research design. Three hundred and seventythree (373) administrative supervisors were studied without sampling. Self-developed questionnairewith 12 items which was face validated by experts in Business Education and Measurement andEvaluation was used for data collection. The reliability of the instrument was determined using pilot testing and data generated analyzed using Cronbach Alpha formula which yielded a correlation valueof .86. Mean, standard deviation, ANOVA and t-test were used for data analysis. Findings showedthat cloud computing competencies were highly required of OTM graduates of polytechnics in NorthEast Nigeria for electronic records management. Years of experience and educational attainment werenot significant factors affecting on the extent cloud computing competencies were required of OTMgraduates of polytechnics for electronic records management. Based on the findings of the study, theresearcher concluded that; OTM graduates in polytechnics in North East, Nigeria highly require cloudcomputing competencies for effective management of records in the educational. institutions. It was recommended among others that; Office Technology and Management (OTM) graduates workinginpolytechnics in Nigeria should be constantly retrained through in-service training, workshops, seminars and conferences to enable them up-date their cloud computing competencies for effectiverecords management.